Using homotopy analysis method for solving fredholm and volterra integral equations - Ibrahim, Issaka (2017)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Philosophy in Pure Mathematics.